Mind Maps As A Visual Teaching Method - Khodjaeva Saodatkhan Saidullaevna (Genius Publishing Group, 2022)
The article reveals the one of the innovative and effective teaching methods as mind maps. Mind maps, which are graphic expression of the processes of multidimensional thinking and therefore are the most natural way of thinking of the human brain. Besides it, it is considered a powerful visual method that provides a universal key to unlocking the potential in everyone’s brain
Keywords: Mind map; effective method; visual method; multidimensional thinking